The first report of Xenorhabdus indica from Steinernema pakistanense: co-phylogenetic study suggests co-speciation between X. indica and its steinernematid nematodes - Bhat, A H; Chaubey, A K; Půža, V (Journal of helminthology, 2019)
During a survey in agricultural fields of the sub-humid region of Meerut district, India, two strains of entomopathogenic nematodes, labelled CS31 and CS32, were isolated using the Galleria baiting technique. Based on morphological and morphometric studies, and molecular data, the nematodes were identified as Steinernema pakistanense, making this finding the first report of this species from India. For the first time, we performed a molecular and biochemical characterization of the bacterial symbiont of S. pakistanense. Furthermore, a co-phylogenetic analysis of the bacteria from the monophyletic clade containing a symbiont of S. pakistanense, together with their nematode hosts, was conducted, to test the degree of nematode-bacteria co-speciation. Both isolates were also tested in a laboratory assay for pathogenicity against two major pests, Helicoverpa armigera and Spodoptera litura. The morphology of the Indian isolates corresponds mainly to the original description, with the only difference being the absence of a mucron in first-generation females and missing epiptygmata in the second generation. The sequences of bacterial recA and gyrB genes have shown that the symbiont of S. pakistanense is closely related to Xenorhabdus indica, which is associated with some other nematodes from the 'bicornutum' group. Co-phylogenetic analysis has shown a remarkable congruence between the nematode and bacterial phylogenies, suggesting that, in some lineages within the Steinernema / Xenorhabdus complex, the nematodes and bacteria have undergone co-speciation. In the virulence assay, both strains caused a 100% mortality of both tested insects after 48 h, even at the lowest doses of 25 infective juveniles per insect, suggesting that S. pakistanense could be considered for use in the biocontrol of these organisms in India.
Keywords: symbióza; Xenorhabdus; dezinsekce; fylogeneze; můry; virulence; Phylogeny; Indie; Insect Control; Virulence; India; Tylenchida; larva; Animals; ženské pohlaví; zvířata; koevoluce; Larva; Symbiosis; Female; Biological Coevolution; Moths